Circular RNA cerebellar degeneration-related protein 1 antisense RNA (Circ-CDR1as) downregulation induced by dexmedetomidine treatment protects hippocampal neurons against hypoxia/reoxygenation injury through the microRNA-28-3p (miR-28-3p)/tumor necrosis factor receptor-associated factor-3 (TRAF3) axis - Junhua Wang (Taylor & Francis Group, 2021)
Cerebral ischemia/reperfusion (CI/R) injury results in serious brain tissue damage, thereby leading to long-term disability and mortality. It has been reported that dexmedetomidine (DEX) exerted neuroprotective effects in CI/R injury. Herein, we intended to investigate whether and how circular RNA (circRNA) cerebellar degeneration-related protein 1 antisense RNA (circ-CDR1as) was involved in the DEX-mediated protection on hippocampal neurons. In our work, the mouse hippocampal neuronal cells (HT-22) were used to construct a hypoxia/reperfusion (H/R) model for CI/R injury. Cell proliferation and apoptosis were evaluated by CCK-8 and flow cytometry. Gene expressions were detected by RT-qPCR. Levels of pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β) were measured by ELISA. The association between miR-28-3p and circ-CDR1as or TRAF3 was verified by dual-luciferase assay. The results indicated that DEX alleviated HT-22 cell dysfunction induced by H/R treatment. In addition, circ-CDR1as was downregulated after DEX treatment and reversed the effects of DEX on the proliferation, apoptosis, and inflammatory responses of H/R-treated HT-22 cells. Circ-CDR1as positively regulated TRAF3 expression via interaction with miR-28-3p in HT-22 cells. Circ-CDR1as aggravated H/R-treated HT-22 cell dysfunction through targeting miR-28-3p. Furthermore, TRAF3 inhibition partly abolished the effect of circ-CDR1as overexpression on cellular activities of H/R-treated HT-22 cells. To sum up, our findings, for the first time, demonstrated that DEX exerted neuroprotective effects on hippocampal neurons against H/R treatment via the circ-CDR1as/miR-28-3p/TRAF3 regulatory network, providing novel therapeutic targets for DEX administration in CI/R treatment.